PENGAWASAN KANTOR OTORITAS WILAYAH VIII PADA STANDAR PELAYANAN PENUMPANG KELAS EKONOMI NIAGA BERJADWAL DALAM NEGERI DI BANDAR UDARA SAM RATULANGI - TAMBINGON, ANITA DEBORA; TAMPI, JOHNNY REVO; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2020)
This research was conducted to explain the supervision on the operational standards of domestic scheduled commercial economy class passenger service procedures by the Territory VIII Airport Authority Office. By using a qualitative design with descriptive analysis, it was found that supervision was carried out using Standard Operating Procedure Inspection Procedures for Scheduled Commerce Route Permits and Passenger Service Classes of Domestic Scheduled Commercial Air Transport Business Services that were adjusted to the Pre-Flight, In-Flight and Post-Flight stages. The conclusion of the research is that the supervision of Region VIII Airport Authority Office on the economy class passenger service standard for commercial air transportation at Sam Ratulangi Airport is done more directly than indirectly. This study recommends a regulation that gives authority to the head of the airport authority office to take action on the negligence of services, the need for the use of digital corporate government in receiving and following up on errors in the application of standard operating procedures for services, the need for coordination and synchronization of supervision programs from the Regional Airport Authority Office VIII with Angkasa Pura II as the manager of Sam Ratulangi Airport and the Airlines operating at Sam Ratulangi Airport. Keywords: Supervision; Standard Operating Procedures; Service